ENERGY SECURITY OF UKRAINE: INCLUSIVE APPROACH IN DEVELOPMENT ASSESSMENT AND RATING RESULTS - KOHUT, Sergey (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article provides an analytical review of the trends of inclusive development of Ukraine in international rankings. Analytical data are presented in terms of components: energy stability, availability of energy supply (adjusted net savings without taking into account losses from carbon emissions and carbon intensity). The structural aspect of Ukraine’s energy supply in the context of providing energy resources is analyzed. The minimum level of alternative energy sources in the energy supply structure is demonstrated. The index of inclusive growth of the economy of Ukraine in comparison with a sample of European countries is presented. The place of Ukraine in the international rating of the IGI Inclusive Development Index is indicated. The main indicators of ensuring inclusive growth of world economies in the structure of the IGI index are presented. The necessity of forming a strategy of sustainable development due to the principles of inclusiveness of the country was established, as it is based on ensuring equal access to opportunities and resources. It is noted that in the management of energy security, the assessment of the constituent resources takes into account the interests of all population groups and a policy is formed that will contribute to the inclusive development of society. It is emphasized that, according to the results of the analysis of a sample of European countries, Ukraine has a sufficiently high carbon intensity index of 347 kg per of GDP, and the adjusted net savings, excluding losses from carbon emissions (% of GDP), is only 1% of GDP. The indicators of the rating of the general electricity supply in Europe were analyzed, in which Ukraine occupies the 8th position for 2021, which, in comparison with other European countries, characterizes a satisfactory level and a sufficiently strong position. Ukraine’s electricity supply by component groups indicates the dominance of the share of natural gas, nuclear energy is in second place, and oil is in third place. All this provided an opportunity to emphasize the need for the formation of sustainable development strategies precisely in the context of strengthening the weak sides of inclusive growth - alternative energy sources. The IGI’s Global Inclusive Development Index study found that more inclusive growth is often not achieved until a certain level of economic growth and prosperity is achieved. However, some developing countries perform better than many developed countries. In 2020, Ukraine had a score of 48.24 points, which indicates the sufficiency of access to education, health care, employment, social protection, gender equality and energy resources for all strata of the population.